Effect of lipid sources with different fatty acid profiles on the intake, performance, and methane emissions of feedlot Nellore steers - Fiorentini, G. [UNESP]; Carvalho, I. P. C. [UNESP]; Messana, J. D. [UNESP]; Castagnino, P. S. [UNESP]; Berndt, A.; Canesin, R. C. [UNESP]; Frighetto, R. T. S.; Berchielli, Telma Teresinha [UNESP] (Amer Soc Animal Science, 2014)
The present study was conducted to evaluate the effect of lipids with different fatty acid profiles on the intake, performance, and enteric CH4 emission of Nellore steers. A total of 45 Nellore animals with an average initial BW of 419 +/- 11 kg (at 15 +/- 2 mo) were distributed in a completely randomized design consisting of 5 treatments and 9 replicates. The roughage feed was maize silage (600 g/kg on a DM basis) plus concentrate (400 g/kg on a DM basis). The dietary treatments were as follows: without additional fat (WF), palm oil (PO), linseed oil (LO), protected fat (PF; Lactoplus), and whole soybeans (WS). The lipid source significantly affected (P < 0.05) nutrient intake. The greatest intakes of DM, OM, and CP were observed in the animals that were fed the WF or PF diets, and the lowest intakes were observed in the animals that were fed the PO diet. Intake of NDF decreased (P < 0.05) with the addition of PO. Enteric methane emission (g/kg DMI) was reduced by an average of 30% when the animals were fed diets containing WS, LO, and PO (P < 0.05), and these diets caused a larger reduction in the energy loss in the form of methane compared to those without added fat and with added PF (3.3 vs. 4.7%). The different fatty acid profiles did not affect the backfat thickness or the loin eye area of the animals (P > 0.05). However, animals fed PO displayed lower daily weight gain (0.36 kg/d), feed efficiency (0.08 kg ADG/kg DM), HCW (245 kg), and hot yield percentage (52.6%) compared to animals that were fed the other diets. Therefore, PO compared to the other lipid sources used in this study reduces intake, performance, feed efficiency, and carcass yield. Therefore, PO is not suggested for feedlot-finished animals.
Keywords: Intake; Linseed oil; palm oil; protected fat; Whole soybean